2007
DOI: 10.1002/art.22817
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and citrullination modifies vimentin to a novel autoantigen for rheumatoid arthritis

Abstract: Objective. Modification of antigens represents a trigger for the generation of autoantibodies. In the pathogenesis of rheumatoid arthritis (RA), citrullination of proteins has been shown to be a critical process, and the determination of antibodies against citrullinated antigens has been a diagnostic milestone. We undertook this study to determine whether antibodies to mutated and citrullinated vimentin (MCV) could serve as a diagnostic and prognostic marker for RA.Methods. We identified novel isoforms of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
240
2
10

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(272 citation statements)
references
References 35 publications
12
240
2
10
Order By: Relevance
“…Keskin et al [21] found that the measurement of serum anti-MCV levels is useful for diagnosis of RA and combined use of anti-MCV and RF antibodies may be more useful prognostic factor than RF and anti-CCP. The discrepancy between various studies can be explained by the difference in: (i) patient populations [22], (ii) early RA [23,24] or established RA [12,25], or (iii) number of cases studied [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keskin et al [21] found that the measurement of serum anti-MCV levels is useful for diagnosis of RA and combined use of anti-MCV and RF antibodies may be more useful prognostic factor than RF and anti-CCP. The discrepancy between various studies can be explained by the difference in: (i) patient populations [22], (ii) early RA [23,24] or established RA [12,25], or (iii) number of cases studied [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted and citrullinated by macrophages undergoing apoptosis, largely present in the RA synovial microenvironment due to impaired clearance [12,13]. Citrullinated vimentin had been identified as potential auto antigen in the pathophysiology of RA and an enzyme-linked immunosorbent assay (ELISA) was developed for the detection of autoantibodies directed against a mutated citrullinated vimentin [2].…”
Section: Introductionmentioning
confidence: 99%
“…A mutated isoform of vimentin was identified by mass spectroscopy analysis of purified vimentin in synovial fluid samples from patients with RA. Subsequently, a human recombinant mutated isoform of vimentin, citrullinated in vitro, was used in a new commercial enzyme-linked immunosorbent assay (ELISA) for detection of the respective antibodies against mutated citrullinated vimentin (anti-MCV) (12). Studies that compared the diagnostic accuracy of anti-MCV and anti-CCP antibodies in RA found comparable sensitivities, while the specificities were higher for anti-CCP in most cases (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Among the proteins that are targeted by APCA, citrullinated vimentin soon became a very promising target because it is present specifically in the pannus and in the synovial fluid of RA patients [22,23]. Therefore, the industry has recently proposed a specific test for antihuman modified citrullinated vimentin (a-MCV) [24].…”
mentioning
confidence: 99%